FUNGSI JAKSA DALAM MENUNTUT TERDAKWA KORUPSI UNTUK PENGEMBALIAN KERUGIAN KEUANGAN NEGARA PERSPEKTIF SISTEM PERADILAN PIDANA INDONESIA - Sinaryati, Ni Wayan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 1 (2015)DO - 10.24843/JMHU.2015.v04.i01.p13, 2015)
This thesis of prosecutor function in the implementation of the court decision related to return of financial loss caused by corruption. In addition, this study also aims to determine and assets the constraints in the implementation of court decisions related to the return of financial loss. It is invecitable that at current time, corruption is one of the remarkable (extra ordinary crime) that endanger the stability and security as well as economic development in Indonesia. Corruption in Indonesia has been so severed and widespread in the community and very alarming, its development continues to increase from year to year, both in number of cases and the amonut of state financial losses and in terms of quality. These cirminal offenses commit more systematic and scope into all aspects of life. Starting from lower level of the dominant and state officials or law enforcement. Judge in imposing sanctions not only imprisonment and also fined an additional punishment, including the return of financial loss to the state by state corruption. The method used in this research is the method of normative juridical legal research of the research using primary and secondary data sources by document. This approact to use the statute approach, the analifical and conseptual approach, case approach and comparative approach legal, basic of corruption in the judicial process is ussed act No. 8 of 1981 (KUHAP), Act No. 31 of 1999, Act No. 20 of 2001 and Act No. 16 of 2004 The constraints in the implementation of the court decision related to the return of states losses, is convicted assets and property that has been transfered, multiple population administration and duration of the judicial proceses of implementation is not effective.
Keywords: Prosecutor Function, To Return Financial Loss, Corruption